Medical Characteristics of Arid-Semi Arid Truffle (Terfezia and Picoa) in the Elazığ-Malatya region of Turkey - Akyüz, Mehmet; Kırbağ, Sevda; Bircan, Burak (My University, 2015)
In this study, the antimicrobial and antioxidant activity of Terfezia boudieri, T. claveryi, T. olbiensis, Picoa lefebvrei and P. juniperi were investigated. It was determined that the methyl alcohol extraction of T. boudieri, T. claveryi, T. olbiensis, P. lefebvrei and P. juniperi inhibit the development of E. coli, B. subtilis, P. aeruginosa, S. aureus, S. mutans, P. vulgaris, S. typhi, C. tropicalis and Trichophyton sp. at various levels (8 mm to 22 mm diameter) and their effect to remove the DPPH radical was more efficient at groups to which samples of 25 ?L (1.22% to 2.58%), 50 ?L (2.31% to 3.28%) and 100 ?L (5.24% to 8.00%) were added. It was determined that methyl alcohol that was extracted from Terfezia species were more effective than Picoa species against test microorganisms. When the groups were compared in terms of concentration, the highest level of free radical scavenging effect at the group, to which we added a 100 ?L sample, was seen at T. boudieri with 8.00%.
Keywords: Mantar Bilimi; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; İmmünoloji